DNA methylation subgroups in melanoma are associated with proliferative and immunological processes. Issue 1 (December 2015) - Lauss, Martin; Ringnér, Markus; Karlsson, Anna; Harbst, Katja; Busch, Christian; Geisler, Jürgen; Lønning, Per; Staaf, Johan; Jönsson, Göran
Abstract Background DNA methylation at CpG dinucleotides is modified in tumorigenesis with potential impact on transcriptional activity. Methods We used the Illumina 450 K platform to evaluate DNA methylation patterns of 50 metastatic melanoma tumors, with matched gene expression data. Results We identified three different methylation groups and validated the groups in independent data from The Cancer Genome Atlas. One group displayed hypermethylation of a developmental promoter set, genome-wide demethylation, increased proliferation and activity of the SWI/SNF complex. A second group had a methylation pattern resembling stromal and leukocyte cells, over-expressed an immune signature and had improved survival rates in metastatic tumors (p < 0.05). A third group had intermediate methylation levels and expressed both proliferative and immune signatures. The methylation groups corresponded to some degree with previously identified gene expression phenotypes. Conclusions Melanoma consists of divergent methylation groups that are distinguished by promoter methylation, proliferation and content of immunological cells.